Massive necrotizing fasciitis following bellow-knee arterial surgery – A therapeutic challenge - Popov, Petar; Tanasković, Slobodan; Sotirović, Vuk; Nenezić, Dragoslav; Radak, Djordje (Vojnosanitetski pregled, 2015)
Introduction. Necrotizing fasciitis is a rare, progressive bacterial infection of superficial fascia followed by secondary subcutaneous tissue necrosis. We pressented a patient with massive fulminant lifethreatening necrotising fasciitis after bellow-knee femoro-popliteal vein bypass grafting successfully treated by antibiotics, surgical debridement and final skin reconstruction using the Tierch method. Case report. A 61-year-old patient was admitted to the Vascular Surgery Clinic for below-knee femoro-popliteal bypass grafting. He complained of intermittent claudication in the left leg after 50 m, ankle brachial indexes were 0.45 on the left and 1.0 on the right side. Femoropopliteal below-knee bypass grafting was done using the autologous great saphenous vein. In the very next day, initial signs of skin infection appeared including local inflammation, erythema, swelling and cellulitis restricted to saphenectomy site. These changes had rapidly spread in the following days on the deep tissue of the whole upper and lower leg, including the groin and with clinical signs of life-threatening systemic infection. Immediate surgical debridement was done followed by extensive wound packing and wide spectrum antibiotics administration for the next 33 days when final skin reconstruction by the Tierch method was performed. Interesting point is that this entire time wound swab was sterile. Conclusion. In the presented case immediate surgical debridement, wide spectrum antibiotics administration and consistent wound packing gave satisfactory results in this life-threatening systemic infection. Wound swab is not always a reliable indicator of the infection while clinical findings and surgeons’ experience are of great significance in rapid reaction to this rare surgical complication.
Keywords: vascular surgical procedures; treatment outcome; fasciitis; necrotizing; anti-bacterial agents